THE APPROACH TO TRAINING LOGGING MACHINERY OPERATORS - Chernykh, Dmitrii; Steshina, Lyudmila; Petukhov, Igor; Andrianov, Yuri; Velev, Dimiter (Journal of Applied Engineering Science, 2022)
The article considers the problem of increasing productivity in harvesting, algorithm for the formation of individual educational trajectories for training operators of logging machines is proposed and the detailed experimental results on practical implementation of developed algorithm are given. The experimental results are checked, verified and efficiency of developed algorithm is proved via various criteria.